Improving Asset Management System On Faculty Of Industrial Engineering Using Scrum Method - Barlean , M Zaidan Rais; Andrawina, Luciana; Anggana, Hilman Dwi (eProceedings of Engineering, 2025)
This research addresses the challenges faced by Telkom University's Faculty of Industrial Engineering (FRI) in managing extensive equipment across multiple buildings due to the reliance on manual methods and fragmented data storage. The study aims to develop an improved Management Information System (MIS) to centralize asset data, streamline workflows, and standardize processes, thereby enhancing asset management efficiency. Utilizing a fishbone diagram, the root causes of existing issues, including shortcomings in people, information, and equipment management, were identified. Relevant literature on asset management and information systems was reviewed to construct a conceptual framework for the proposed solution. The implementation of the improved MIS is expected to facilitate easy access to asset information, automate workflows, and enable comprehensive asset lifecycle tracking, leading to optimized maintenance schedules, reduced equipment downtime, and cost savings. The research concludes that the proposed MIS will significantly benefit all stakeholders within FRI by providing a robust, efficient, and centralized system for managing assets, thereby addressing the complex management needs of a university environment. Keyword— Management Information System, Maintenance, Asset Management